Effects of Ten Sessions of High Frequency Repetitive Transcranial Magnetic Stimulation (HF-rTMS) Add-on Treatment on Impulsivity in Alcohol Use Disorder - Schluter, Renée S.; van Holst, Ruth J.; Goudriaan, Anna E. (Frontiers in Neuroscience, 2019)
Introduction: Alcohol use disorder is characterized by increased impulsivity, which is multifactorial and can be assessed by tests like the delay discounting, Go-NoGo, and stop signal task. Impulsivity has been related to poor treatment outcomes in substance use disorders, including alcohol use disorder. In order to decrease impulsivity or improve inhibitory control, high frequency transcranial magnetic stimulation (HF-rTMS) has gained interest. Studies applying HF-rTMS over the DLPFC of individuals suffering from alcohol use disorder assessing its effects on impulsivity measures are scarce, and results are inconclusive. Methods: The current study (registered in The Netherlands Trial Register with trial number 5291: https://www.trialregister.nl/trial/5151) applied ten sessions of HF-rTMS (sixty 10 Hz trains of five seconds at 110% motor threshold) over the right DLPFC of 80 alcohol dependent patients in clinical treatment on ten consecutive workdays. At baseline, halfway and after the HF-rTMS treatment, the delay discounting, Go-NoGo, and stop signal task were assessed. Results: Ten sessions of HF-rTMS over the right DLPFC versus sham HF-rTMS did not affect performance on the delay discounting, Go-NoGo, and stop signal tasks. A significant effect of age was found for the Go-NoGo task, with higher age associated with better performance. Furthermore, no significant correlations were found between difference scores of task performance and baseline impulsivity or severity of AUD. Discussion: Results of this study, in combination with other studies using HF-rTMS studies in alcohol and substance use disorder, indicate mixed and inconclusive findings of HF-rTMS on impulsivity. Future studies within patient groups hospitalized at the same department are recommended to consider using a sham coil that mimics the sensations on the scalp of active HF-rTMS and to measure motivation across test sessions.